The Effect of Process Temperature and Holding Time on Weldability in Diffusion Welding of Duplex Stainless Steels and Marine Grade Steels for Oil and Gas Pipes - Baharudin, B.A. (Springer Science and Business Media Deutschland GmbH, 2022)
Diffusion welding is done on specimens of duplex stainless steel and low carbon steel under varied temperature and holding time. The specimens were clamped using jigs and pre-pressed at 10 MPa and heated in a furnace. Impact test were performed on the joined samples. The effect of process temperature and holding time on the impact strength of the diffusion welds were observed. The impact strength of the joints was examined, and the highest value of 0.9 J is obtained at a temperature of 1050 Â°C and holding time of 240 min. Â© The Author(s), under exclusive license to Springer Nature Switzerland AG 2022.